2015
DOI: 10.14295/2238-6416.v70i2.401
|View full text |Cite
|
Sign up to set email alerts
|

Identificação De Bactérias Psicrotróficas Proteolíticas Isoladas De Leite Cru Refrigerado E Caracterização Do Seu Potencial Deteriorador

Abstract: RESUMOOs objetivos deste estudo foram identificar bactérias psicrotróficas proteolíticas isoladas de leite cru refrigerado, avaliar o seu poder deteriorador e a sua capacidade de adesão em superfícies de aço inoxidável sob temperaturas de refrigeração. Dentre as bactérias gram-positivas, 23,81% e 33,33% dos isolados pertenciam aos gêneros Bacillus e Paenibacillus respectivamente. No grupo de bactérias gram-negativas fermentadoras de glicose foram identificados os gêneros Cedecea, Enterobacter, Hafnia, Klebsiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Ao avaliar bactérias psicrotróficas em leite cru refrigerado e seu poder de adesão em aço inoxidável, Oliveira Pinto et al (2015), encontraram em seus estudos que 23,81% dos isolados pertenciam ao gênero Bacillus e 33,33% Paenibacillus, demonstrou que todos os isolados, produziam proteases, lipases e lecitinases, e verificou adesão na superfície de aço inoxidável. Ressaltou a importância das boas práticas no campo e na indústria para que dessa forma minimize a perda econômica.…”
Section: Resultsunclassified
“…Ao avaliar bactérias psicrotróficas em leite cru refrigerado e seu poder de adesão em aço inoxidável, Oliveira Pinto et al (2015), encontraram em seus estudos que 23,81% dos isolados pertenciam ao gênero Bacillus e 33,33% Paenibacillus, demonstrou que todos os isolados, produziam proteases, lipases e lecitinases, e verificou adesão na superfície de aço inoxidável. Ressaltou a importância das boas práticas no campo e na indústria para que dessa forma minimize a perda econômica.…”
Section: Resultsunclassified
“…Sample preparation was performed according to the procedures described by Frank et al (1992). The counting of proteolytic psychrotrophic and psychrotrophic microorganisms was performed according to Pinto et al (2015) with changes in the incubation conditions. After serial dilutions in peptone-salt solution (0.85% w/v NaCl; 0.1% w/v bacteriological peptone), samples were plated onto Plate Count Agar (PCA) supplemented with 2% w/v skimmed milk powder.…”
Section: Enumeration Of Proteolytic Psychrotrophic and Psychrotrophic Microorganismsmentioning
confidence: 99%
“…The dominant genera observed during the days of the three treatments belonged to two classes, Gammaproteobacteria and Bacilli, with the class Gammaproteobacteria being dominant in almost every day, with an approximate average of 85% of the relative abundance (Figure 5A). The contaminating microbiota of refrigerated raw milk includes both Gram-positive and Gram-negative microorganisms, but the latter represents more than 75%, among which a large part belong to the Gammaproteobacteria class (Nörnberg et al 2011;Pinto et al 2015). observed that in the biofilms formed by the microbiota of raw milk at 7 ºC, Gammaproteobacteria and Bacilli represented about 50% each of the microorganisms identified.…”
Section: Microbial Diversity Of Biofilmmentioning
confidence: 94%
“…Due to the high microbial diversity in raw milk, biofilms on the surfaces of equipment and pipes in the dairy industries can be formed by more than one species interacting in a microbial community (Latorre et al 2010;. It is known that the Gram-negative bacteria represent more than 75% of the microbiota of refrigerated raw milk (Pinto et al 2015;. However, cells adhered to stainless steel (SS) surfaces in the pre-pasteurization and post-pasteurization ducts of a milk processing plant were identified as 56% Gram-positive, while the other 44% were Gram-negative (Cherif-Antar et al 2016).…”
Section: Introductionmentioning
confidence: 99%